Vividação na pele restaurada : limite entre o viver e o morrer do paciente grande queimado e o cuidado da equipe hospitalar - Souza, Josélia Quintas Silva de (2003)
The main goal of this research is to reflect on the severely-burned patient who is in a limit situation and who has been offered current psychological help, so that he/she is able to face the necessary treatment. This severe health situation leads the patient into a deep depression and consequently makes him/her feel that his/her life may come to an end some time in the near future. Therefore the severely-ill patients feel themselves depressed and helpless. Because they underwent very serious burns and due to their high level of morbidity they feel emotinally impaired. They need strength so that they are able to stand and face treatment. Moreover, they need to be conscious of their own deep suffering in order to face it with courage and in a positive way. The methodology chosen has a phenomenal and existential basis. Hence interviews were made with the patients and the medical staff as well so that one can understand how this tough experience happens and also what it means to the patient. Based on the patients report it was found that they feel anxious and anguished both for not knowing what is ahead for them, e. g. if they will get better and also because they are aware of death: they know they may die! The author decides to name vividação that very situation which Frankl mentions when the patients make use of their own courage, hope and sympathy to overcome anxiety and suffering. Heidegger thinks that anguish and anxiety both force the patients to care for themselves, and turn them strong in their deep inner loneliness. This fact shows that vividação is in fact ação vivida , e. g. the patients themselves fighting to defeat all that anguish, anxiety and suffering